2021
DOI: 10.3892/etm.2021.10207
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic neuropathic pain induced by streptozotocin alters the expression profile of non‑coding RNAs in the spinal cord of mice as determined by sequencing analysis

Abstract: Diabetic neuropathic pain (DNP) is one of the most serious complications of diabetes. Patients with DNP always exhibit spontaneous and stimulus-evoked pain. However, the pathogenesis of DNP remains to be fully elucidated. Non-coding RNAs (ncRNAs) serve important roles in several cellular processes and dysregulated expression may result in the development of several diseases, including DNP. Although ncRNAs have been suggested to be involved in the pathogenesis of DNP, their precise roles remain to be determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Recently, He et al performed RNA sequencing to study the expression patterns of circRNAs, lncRNAs and miRNAs in the spinal cord of streptozotocin‐induced diabetic neuropathic pain (DNP) mice. 52 They found that there were 135 circRNAs were differentially expressed and 71 circRNAs were downregulated and 64 circRNAs were overexpressed in spinal cord between control group and DNP group. Amongst these, circ_0010794, circ_0006623, circ_0006175, circ_0007095, circ_0005297, circ_0012840 and circ_0001580 was overexpressed and circ_0016083, circ_0006471, circ_0008757, circ_0004843 and circ_0013996 was downregulated (Figure 1 and Table 1 ).…”
Section: Circrna Expression Profiling and Integrative Analysis In Neuropathic Painmentioning
confidence: 98%
“…Recently, He et al performed RNA sequencing to study the expression patterns of circRNAs, lncRNAs and miRNAs in the spinal cord of streptozotocin‐induced diabetic neuropathic pain (DNP) mice. 52 They found that there were 135 circRNAs were differentially expressed and 71 circRNAs were downregulated and 64 circRNAs were overexpressed in spinal cord between control group and DNP group. Amongst these, circ_0010794, circ_0006623, circ_0006175, circ_0007095, circ_0005297, circ_0012840 and circ_0001580 was overexpressed and circ_0016083, circ_0006471, circ_0008757, circ_0004843 and circ_0013996 was downregulated (Figure 1 and Table 1 ).…”
Section: Circrna Expression Profiling and Integrative Analysis In Neuropathic Painmentioning
confidence: 98%
“…In the spinal cord, numerous miRNA expression changes have been observed in chronic constriction injury (CCI) and diabetic neuropathic pain (DNP) rodents. [23][24][25][26] Previous research has suggested some miRNAs may be related to neuropathic pain development, for example, miR-500, -221, and -21, 25 thus, acting as potential targets in its treatment. 27 Cytoscape software constructed the miRNA-target gene regulatory network in the supraspinal region, including the nucleus accumbens (NAc), medial prefrontal cortex, and periaqueductal gray, between SNI and sham rats.…”
Section: Mirnas Expression Changesmentioning
confidence: 99%
“…The spinal cord dorsal horn relays and modulates pain signals from the peripheral nociceptors to the supraspinal regions. In the spinal cord, numerous miRNA expression changes have been observed in chronic constriction injury (CCI) and diabetic neuropathic pain (DNP) rodents 23–26 . Previous research has suggested some miRNAs may be related to neuropathic pain development, for example, miR‐500, ‐221, and ‐21, 25 thus, acting as potential targets in its treatment 27 …”
Section: Peripheral Nerve Injury or Noxious Stimuli Induce Extensive ...mentioning
confidence: 99%
“…With this technique, Xiong and colleagues were able to identify a total of 374 circRNA differentially expressed in the DRG of rats following the induction of neuropathic pain by CCI (preprint here: [ 55 ]). This approach has also been used to identify differentially expressed miRNA, lncRNAs and circRNAs in the spinal cord of a model of diabetic neuropathic pain [ 59 ]; lncRNAs and mRNA in the spinal cord of rats subjected to paclitaxel-induced peripheral neuropathy [ 52 ]; and miRNA and mRNA in the DRG of rats between a CCI group and a CCI-exercise group [ 73 ]. However, RNA-Seq techniques may suffer from PCR-related bias, including library preparation and sequencing errors [ 161 ].…”
Section: Non-coding Rnas and Painmentioning
confidence: 99%